Valuation of linkages between climate change, biodiversity and productivity of European agro-ecosystems - Ruslana Rachel Palatnik; Paulo Augusto Lourenço Dias Nunes (Fondazione Eni Enrico Mattei (FEEM), 2010)
It is clear that climate change involves changes in temperature and precipitation and therefore directly affects land productivity. However, this is not the only channel for climatic change to affect agro-systems. Biodiversity is subject to climatic fluctuations and in turn may alter land productivity too. Firstly, biodiversity is an input into agro-ecosystems. Secondly, biodiversity supports the functioning of these systems (e.g. the balancing of the nutrient cycle). Thirdly, agro-systems also host important wildlife species which, though not always, play a functional role in land productivity, nonetheless constitute important sources of landscape amenities. The present paper illustrates a unique attempt to economically assess this additional effect climate change may imply on agriculture. We first empirically evaluate changes in land productivity due to climatic change effect on temperature, precipitations and biodiversity. Then we estimate the economic cost of biodiversity impact on agro-systems. Our key finding is that climate-change-induced biodiversity impact on European agro-systems measured in terms of GDP change in year 2050 is sufficiently large to deepen the direct climate-change effect in some regions and to reverse it in others. Different economies show different resilience profiles to deal with this effect.
Keywords: D58; Q54; Q57; 330; Climate Change; Biodiversity; Agro-Ecosystems